Narratives on leaving care in Switzerland: Biographies and discourses in the 20th century. - Keller, Samuel; Gabriel, Thomas; Bombach, Clara (Child & Family Social Work, 2021)
Research on institutional care and its long‐term effect on life trajectories provides crucial and sometimes unexpected insights. In a qualitative study in Switzerland, we have conducted 37 narrative interviews with people who experienced residential care between 1950 and 1990. The analysis was based on a reconstructive life course perspective and grounded theory. The findings show a complex interplay of residential care context (here: narratives from expert discourses) and intersubjective experiences during and after care. Most interviewees learned from their experiences to be sceptical of social relationships and of all kinds of state interventions—even decades after having left. A few were able to take charge of their lives and steer them in an individually successful direction. In these cases too, results point to fragile concepts of success. Thus, critical questions about residential care in these decades remain. We suggest that rather than abolish residential care facilities, we need to gather more evidence about the factors that contribute to high‐quality out‐of‐home‐placements. As professional settings, they can enable young people individually. They need to avoid responding to children as 'objects of care', by neglecting all subjective dimensions and reproducing a pattern of powerlessness with a strong focus on formal, measurable goals.